Modernizing the mainframe unleashing the power of XML and web services. - Gentry, Joe
Central Hudson Gas and Electric, a New York State utility company, wanted to find a way to improve its customer service by creating a Web-based platform where customers could view and retrieve bills online. Replacing or rewriting the company's 20-year old mainframe billing application wasn't an option. The mainframe worked great and could satisfy the company's growth plans for some time to come.